Let y = (x-3) / (x+7). Then this equation can be expressed in the form (x+a)(y+b) = c for some constants a, b, and c. Enter your answer in the form a, b, c

Guest Apr 10, 2023

#1**0 **

Here are the steps on how to express the equation y=x+7x−3 in the form (x+a)(y+b)=c:

Multiply both sides of the equation by x+7.

(x+7)y=x−3

Distribute the x+7 on the left-hand side of the equation.

xy+7y=x−3

Factor out x from the left-hand side of the equation.

x(y+7)=x−3

Subtract x from both sides of the equation.

x(y+7)−x=x−3−x

Simplify the left-hand side of the equation.

xy+7=−3

Rewrite the equation in the form (x+a)(y+b)=c.

(x+0)(y+7)=−3

Therefore, the constants a, b, and c are 0,7,−3.

Guest Apr 10, 2023